О двух классах прецессионных движений гиростата под действием потенциальных и гироскопических сил - Щетинина, Е.К. (Нелінійні коливання, 2011)
Отримано два нових класи прецесiйних рухiв гiростата з нерухомою точкою, що описуються диференцiальними рiвняннями Кiрхгофа. Для першого класу швидкостi прецесiї i власного обертання рiвнi мiж собою i заданi у виглядi тригонометричного многочлена першого степеня вiдносно кута власного обертання. Для другого класу швидкостi прецесiї й обертання не збiгаються мiж собою i визначенi спецiальними залежностями вiд кута власного обертання. Данi класи прецесiй описуються новими розв’язками рiвнянь Кiрхгофа. We find two new classes of precession motions of a gyrostat with a fixed point. The motions are described by Kirchhoff’s differential equations. For the first class, the precession velocity and the eigen rotation velocity are equal and given by a first order trigonometric polynomial in the angle of the eigen rotation. For the second class, the procession and the rotation velocities do not coincide, and are given by special functions of the angle of proper rotations. These classes are described in terms of new solutions of Kirchhoff’s equations.